SECONDARY SCHOOL ENGLISH TEACHERS’ PRECEPTION TOWARDS THE USE OF FLIPPED LEARNING IN BULELENG REGENCY - Handayani, D. K. Putri; Santosa, M. H.; Saputra, I N. P. Hadi (Journal of Education Research and Evaluation, 2020)
This study is aimed at (1) investigating the perception of secondary school English teachers? perception towards the use of Flipped Learning in Buleleng regency, (2) observing the problems that the teachers encountered during implementing Flipped Learning, and (3) evaluating the solutions that the teachers do to solve the problems. This study was a mixed-method research design which used cross-sectional survey as the method. Purposive sampling was employed to four secondary English teachers who apply Flipped Learning. They came from three public secondary schools in Buleleng regency. This study used a questionnaire and an interview guide as instruments which had been tested for its validity and reliability. The data from the questionnaires were processed by using Arithmetic Statistics in Microsoft Office Excel to calculate the mean score in order to know the qualification level of each perception. The results of data analysis indicated that most of teachers corresponded to very positive perception on the use of Flipped Learning since the mean score was 81.25 which categorized to very high category. The results imply that Flipped Learning is highly recommended to be implemented in the English teaching and learning process.